2018
DOI: 10.1080/10837450.2018.1514522
|View full text |Cite
|
Sign up to set email alerts
|

Development of filaments for fused deposition modeling 3D printing with medical grade poly(lactic-co-glycolic acid) copolymers

Abstract: The manufacturing of custom implants and patient-tailored drug dosage forms with fused deposition modeling (FDM) three-dimensional (3D) printing is currently considered to be very promising. Most FDM printers are designed as an open filament system, for which filaments with a defined size are required. In addition to this processing requirement, the filament material must be of medical or pharmaceutical quality, in order to be suitable in these applications. In this work, filaments with nominal diameters of 1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 27 publications
3
14
0
Order By: Relevance
“…The elasticity of the filaments was evaluated based on the Young's modulus values. The values obtained for itraconazole-loaded filaments were in the range 2042.1-2641.1 MPa and they were comparable to the results obtained by Feuerbach et al for Resomer filaments [73]. The filament elasticity was not significantly affected by the addition of either copovidone or crospovidone to the formulation, while the values of the Young's modulus varied in the narrow range.…”
Section: Discussionsupporting
confidence: 86%
“…The elasticity of the filaments was evaluated based on the Young's modulus values. The values obtained for itraconazole-loaded filaments were in the range 2042.1-2641.1 MPa and they were comparable to the results obtained by Feuerbach et al for Resomer filaments [73]. The filament elasticity was not significantly affected by the addition of either copovidone or crospovidone to the formulation, while the values of the Young's modulus varied in the narrow range.…”
Section: Discussionsupporting
confidence: 86%
“…Hence, it can be concluded that the MFR values of the order of ~20–30 g 10min −1 (at a temperature range of 200–210 °C and 5 kg load) allow to pre-qualify the studied TPU filaments as suitable for 3D printing with the FFF/FDM method. However, it should be remembered that to fully assess the suitability of the filament for 3D printing, the results of tests such as thermal, rheological or mechanical should be taken into account [ 23 , 24 , 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…In literature, the target diameter was achieved by stretching and cooling the filament on conveyer belts [13][14][15][16][17]. Monitoring of the filament diameter was done with either calipers [6,11,18], offline after extrusion, at line [9,19,20] or inline [4,14], using diameter measurement modules as depicted in Figure 1. A prerequisite for diameter adaption via a conveyer belt is proper adhesion of the filament to the belt to obtain a reproducible and representative diameter.…”
Section: Introductionmentioning
confidence: 99%